Bibliometric Mapping of Research on Magic Towns of Mexico - Flores-Romero, Martha B.; Pérez-Romero, Miriam E.; Álvarez-García, José; del Río-Rama, María de la Cruz (Land (Basel), 2021)
The tourism program “Pueblos Mágicos” was created in 2001 by the Mexican Secretary of Tourism (Sectur), together with its brand, with the aim of promoting tourism by preserving secular and ancestral traditions, as well as revitalizing cities and towns that make great efforts to protect and safeguard their cultural wealth. In this context, the aim of this research work is to show the current state of scientific research carried out within the context of the Magic Towns of Mexico. The work methodology is based on the bibliometric analysis of the scientific production indexed in two main international databases: Web of Science and Scopus. The application of this technique will make it possible to obtain a scientific mapping of the production (growth, researchers in the subject, production impact through the number of citations, network analysis, etc.), with the aim of observing the evolution in the generation of knowledge regarding this tourism development tool that acts as a distinctive brand for tourism in Mexico. This mapping is useful for researchers as it provides information on the research carried out so far, allowing them to identify gaps to work on in their future research work. The systematic search process identified 52 articles. The results indicate that the research carried out in this context is incipient, with few researchers addressing the subject on a continuous basis and most of them being transient researchers with a single article. Most of the research was approached from the perspective of cultural heritage, cultural resources, inherited resources, cultural tourism, public policy, local development and sustainable tourism, and sustainable development. In light of the number of articles published, all of these can be considered to be incipient lines of research.